Gender and White-Collar Crime – Theoretical Issues - Galvin, Miranda A. (Criminal justice studies, 2020)
In the mid-1970s, scholars theorized that as women’s lives grew beyond traditional gendered constraints their involvement in crime would come to resemble that of men. Key to some arguments was that women’s increasing involvement in workplaces would provide criminal opportunity. Yet, there has been limited attention paid to the issue of gender in white-collar research. This article discusses the implications of the research in this special issue and also identifies a number of important theoretical issues that white-collar scholars should be attentive to moving forward. It is critical that research should continue to problematize not only the incidence of female involvement in white-collar crime but also the qualities of that involvement. Further, scholars should also be reflective and consider the degree to which their hypotheses related to women’s involvement in crime inherently assume that white masculine identities are the baseline to which women’s behavior will adapt.